Polyelectrolyte gels comprising a lipophilic, cost-effective aluminate as fluorine-free absorbents for chlorinated hydrocarbons and diesel fuel - Wrede, Michael; Frank, Viktoria; Bucher, Janina; Straub, Bernd Franz (ACS applied materials & interfaces, 2012)
Superabsorbent polymers comprising a lipophilic, halogen-free, and cost-effective aluminate (“altebate”) anion have been synthesized. The polyelectrolytes are based on octadecyl acrylate monomers, 0.8-1 mol % ethylene dimethacrylate cross-linker, and 5 mol % N-3-acroyloxypropyl trialkylammonium altebate. At 30 °C, swelling degrees of 70 (chlorobenzene), 102 (CHCl3), 130 (THF), 163 (ClCH2CH2Cl), 171 (dichlorobenzene), and 208 (CH2Cl2) have been determined. The polyelectrolyte absorbs reversibly diesel fuel with a swelling degree of 34, even in the presence of water. Swelling times and critical swelling temperatures have also been determined. The challenges for the development of oil absorbents are discussed.